2020
DOI: 10.17533/udea.ikala.v25n01a06
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Critical Intercultural Awareness Among EFL Students Through Critical Discourse Analysis

Abstract: Fomento de la consciencia crítica intercultural en estudiantes de inglés como lengua extranjera mediante el análisis crítico del discurso Promouvoir la conscience critique interculturelle chez des étudiants en anglais langue étrangère en utilisant l' analyse critique du discours Abstract This paper reports some findings on the development of critical intercultural awareness among English-as-a-foreign-language students in the context of a critical reading enrichment course for students in the preparatory year a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…As a result, students may feel less motivated to hone their digital literacy skills actively. Educational institutions need to recognize the central role of digital literacy in preparing students to face an increasingly digitalized world (Hazaea & Hazaea, 2020). By encouraging the integration of digital literacy in the curriculum, institutions can strongly encourage students to perceive it as an important and relevant competency.…”
Section: Lack Of Integration In the Curriculummentioning
confidence: 99%
“…As a result, students may feel less motivated to hone their digital literacy skills actively. Educational institutions need to recognize the central role of digital literacy in preparing students to face an increasingly digitalized world (Hazaea & Hazaea, 2020). By encouraging the integration of digital literacy in the curriculum, institutions can strongly encourage students to perceive it as an important and relevant competency.…”
Section: Lack Of Integration In the Curriculummentioning
confidence: 99%
“…It is a primary cognitive tool for adapting to and assimilating the dynamic global culture and economy. Saudi English educators should foster critical thinking (Al Zahrani & Elyas, 2017;Hazaea, 2020) in the process of reformulating the learning goals and instructional procedures to enhance the growth of language competence (Bá ez, 2004). Critical thinking developed through EFL learning can equip the Muslim Arabs with moral and philosophical insights of Western epistemology that can enable them to propagate the Islamic values with convincing rhetoric in the language of the foreigner.…”
Section: The Strategic Steps Of Improvement To Fulfill Saudi Vision 2...mentioning
confidence: 99%
“…Their findings showed that two-thirds of the participants moved beyond basic cultural awareness and shifted from their taken-for-granted and stereotypical view of culture to newer perspectives recognizing its relative and dynamic nature. Hazaea (2018) researched the impact of using a critical discourse analysis tool for in-depth reading of the selected text on EFL learners' ICA, and findings showed that the tool helped learners appreciate their own and other cultures and raised their ICA. Farrokh (2019) employed the ethnography of communication model to investigate its effect on intermediate English language learners' reading comprehension.…”
Section: Readers As Text-ethnographers (Rate)mentioning
confidence: 99%